2008
DOI: 10.1038/nature06604
|View full text |Cite|
|
Sign up to set email alerts
|

Hax1-mediated processing of HtrA2 by Parl allows survival of lymphocytes and neurons

Abstract: Cytokines affect a variety of cellular functions, including regulation of cell numbers by suppression of programmed cell death. Suppression of apoptosis requires receptor signalling through the activation of Janus kinases and the subsequent regulation of members of the B-cell lymphoma 2 (Bcl-2) family. Here we demonstrate that a Bcl-2-family-related protein, Hax1, is required to suppress apoptosis in lymphocytes and neurons. Suppression requires the interaction of Hax1 with the mitochondrial proteases Parl (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
179
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(195 citation statements)
references
References 27 publications
8
179
6
Order By: Relevance
“…Although mitochondrial insertion of GrB has not been previously reported, a recent seminal study (52) demonstrated the insertion of another granzyme, GrA, into the mitochondrial matrix, when it is applied directly on isolated mitochondria or together with perforin onto target cells. The resistance of Hax-1 to mitochondrial treatment with proteinase K in association with its release from GrB-treated mitochondria are in line with previous reports on the potential localization of Hax-1 on the mitochondrial inner membrane facing the intermembrane space (28). Thus, Hax-1 cross-talk with the mitochondrial matrix protein, Cyp-D, may take place on the mitochondrial inner membrane.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although mitochondrial insertion of GrB has not been previously reported, a recent seminal study (52) demonstrated the insertion of another granzyme, GrA, into the mitochondrial matrix, when it is applied directly on isolated mitochondria or together with perforin onto target cells. The resistance of Hax-1 to mitochondrial treatment with proteinase K in association with its release from GrB-treated mitochondria are in line with previous reports on the potential localization of Hax-1 on the mitochondrial inner membrane facing the intermembrane space (28). Thus, Hax-1 cross-talk with the mitochondrial matrix protein, Cyp-D, may take place on the mitochondrial inner membrane.…”
Section: Discussionsupporting
confidence: 90%
“…However, compared with fibroblasts from normal donors, stressed Hax-1-deficient fibroblasts from severe congenital neutropenia patients showed a more rapid loss of their membrane potential, suggesting that Hax-1-mediated stabilization of the MMP is not limited to neutrophils (23). Indeed, the likelihood that Hax-1 acts as a mitochondrial antiapoptotic protein in other cells has been verified by a Hax-1-null mouse model (28). Loss of Hax-1 resulted in postnatal lethality as well as lymphocyte and neuron apoptosis.…”
mentioning
confidence: 99%
“…However, we could not detect any HAX-1 cleavage product(s) in the current study (the same source of anti-HAX-1 antibody was used). The expression of HAX-1 was recently shown to be regulated by cytokines, suggesting a level of transcriptional control of HAX-1 (26). Moreover, as mentioned in the preceding section, TPCK is known to suppress the transcription factor, NF-B.…”
Section: Hax-1 Down-regulation Occurs At the Transcriptional Level Anmentioning
confidence: 87%
“…HS1 and HAX-1 (HS1-associated protein X-1) are both expressed in B cells, and Suzuki et al (32) speculated that HAX-1 could participate in transduction of the signal from the B cell receptor to intracellular organelles, including mitochondria and endoplasmic reticulum. Furthermore, overexpression of HAX-1 has been reported to block apoptosis in various cell types (14,(22)(23)(24), and homozygous HAX1 deficiency in mice results in postnatal lethality with extensive apoptosis of neurons in the striatum and cerebellum (26). HAX-1 is sometimes classified as a Bcl-2 family protein, based on its structural similarity to Bcl-2 and its mitochondrial localization (32).…”
Section: Discussionmentioning
confidence: 99%
“…Their development was not obviously perturbed but they present an early neurodegenerative disorder with a parkinsonian phenotype [57]. As for some other IMS proteins, Omi seems to have at least two distinct roles, a physiological anti-apoptotic role via mitochondria protection under some stresses, [58,59] and a death effector role, via the inhibition of IAPs, and also, maybe, via the cleavage of other substrates [56].…”
Section: Contribution Of Momp To Caspase-independent Cell Deathmentioning
confidence: 99%